10. Serum vascular endothelial growth factor levels and some characteristics of diabetic retinopathy patients - Nga, Vu Van; Minh, Nguyen Thi Binh; Dung, Dinh Thi My; Anh, Nguyen Thi Lan; Ha, Hoang Thi Thu; Phuong, Le Thi Minh; Hang, Do Thi Le; Quynh, Do Thi; An, Pham Thi Thuy; Thanh, Le Ngoc; Khanh, Tran Van; Thom, Vu Thi (Tạp chí Nghiên cứu Y học, 2024)
Diabetic retinopathy (DR) is a dangerous microvascular complication of diabetes mellitus (DM). The escalating prevalence of diabetes increases the rate of DR patients in Vietnam. Numerous studies have indicated that serum vascular endothelial growth factor (VEGF) can be used as a marker for monitoring the progression of this disease. Our study included 150 diabetic patients and 75 healthy individuals in the control group. Our study included 150 diabetic patients and a control group of 75 healthy individuals. We investigated the association between serum VEGF levels and some characteristics in diabetic retinopathy patients. Clinical data (pulse, blood pressure, medical history, and body mass index) and paraclinical data (Glucose, HbA1c) were collected. Serum samples were analyzed to determine VEGF concentrations. Our study fond that serum VEGF levels were higher in the group with DR compared to the other two groups and exhibited a correlation with glucose levels in diabetic patients (p < 0.05).